Georgia Architectural and Historic Properties Survey of 909 W. Magnolia St., Valdosta, Ga., October 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 909 W. Magnolia St., Valdosta, Ga., October 1980. One story wood frame house (L-shape) with multi-gabled roof. Gabled porch , exposed rafters, sitting on brick piers. Double hung sash windows with 6/6 lights. Shiplap siding. Interior chimney. Fair condition. Date of Construction: App. 1915-1925. Not significant as part of a district. Modern intrusions add to the feeling that this area does not hold together well.
Georgia Architectural and Historic Properties Survey of 909 W. Magnolia St., Valdosta, Ga., October 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 4 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 105 MB (110,785,362 bytes). Note: 2 copies in separate folders, combined.
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)